Capital requirements and lending activity of banks in the US, Europe and Asia - Dang, Anh (2018)
Capital ratio requirements have important impact on bank lending activities. This thesis studies and compares the relationship between capital ratio and lending growth, practice in loan loss provisions and changes in fee income ratio among the three geographical areas. The results suggest that, in general, Tier 1 capital plays a positive role in supporting lending growth, and Tier 2 capital does not. The effect of Tier 1 capital is statistically significant for small size banks in all three areas. When lending grows in economic upswings, US and European banks tend to make lower loan loss provisions while Asian banks tend to reserve more. Increase in fee income ratio associated with decrease in lending is found among banks in the US and Europe, who experience sharp decline in lending. This negative relation is not found for the case of Asian banks.